Cultural Goods Consumption and Cultural Capital - Rüdiger Pethig; Sao-Wen Cheng (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2000)
Cultural capital is assumed to benefit all members of society. It is built up by the aggregate consumption of cultural goods and is diminished through depreciation. In the no-policy market economy, consumers tend to ignore the beneficial external effects of their cultural good consumption on the other consumers (and on themselves) through augmenting cultural capital. Cultural goods will be less consumed and, as a result, cultural capital will be underprovided. The efficient allocation is shown to be restored by an appropriate subsidy on cultural goods that stimulates the consumers demand for cultural goods and thus promotes the accumulation of cultural capital.
Keywords: 330; Kulturgüter; Öffentliche Güter; Kulturökonomik; Externer Effekt; Kulturpolitik; Theorie